STRUKTUR NANOKRISTAL CeO YANG DISINTESIS MENGGUNAKAN METODE PRESIPITASI DENGAN VARIASI LAMA WAKTU KALSINASI 2 - Nursanti, Ida; Muhlisin, Zaenul; Sutanto, Heri; Nurhasanah, Iis (BERKALA FISIKA, 2011)
Nanocrystalline CeO have been synthesized by using a precipitation method. in a mixedsolvent system of aqua DM and isopropanol. Precipited was calcined at temperature of 300 C forvarious calcination time. X-ray difractometer was used to investigate resulting presipitedmicrostructure. X-ray diffraction patterns were analyzed to study effect of calcination time tostructure and crystallite size. Refinement process of x-ray diffraction pattern was carried out byusing Rietveld method. The results show that all of precipited were CeO nanocrystalline withsingle phase of cubic fluorite. The difference in lattice parameter was correlated to oxygenvacancy. Crystallite size was found in the range 9 – 11 nm, its incresed as calcination timeincreased. The increasing of calcination time did not significant influence to crystallite size. These result indicated that CeO nanocrystalline exhibited weak-agglomeration.Keywords: CeO222, nanocrystalline, microstructure, x-ray diffraction, precipitation 2o